Diversity and distribution of amino acid decarboxylase enzymes in the human gut bacteria—a bioinformatics investigation - Sandoval, Matthew; Shah, Dhara D. (Frontiers in Microbiology, 2025)
Biogenic amines play numerous biological functions that include neuromodulation, maintenance of the gut health and motility, gastric acid secretion, regulation of immune response, cell growth, and gene expression. Therefore, it is crucial to comprehend the potential modulation of these molecules by the human gut microbiota. A primary pathway for the generation of these molecules involves the decarboxylation of amino acids, a process facilitated by enzymes known as amino acid decarboxylases (AADCs). Here, we conducted a bioinformatic analysis to understand diversity and prevalence of AADCs from the most prevalent members of the human gut microbiome. This study aims to understand how human gut microbes generate metabolites that influence health and disease, through specific enzyme activities. Our results indicate that AADCs are most abundant in the prominent gut microbial genera, namely Bacteroides, Parabacteroides, Alistipes, and Enterococcus. Within these, Enterococcus faecalis harbors the most variety of amino acid decarboxylases, potentially playing an important role in driving decarboxylation chemistry in the human gut. Furthermore, among AADCs, arginine decarboxylases are the most common, present in approximately 60% of the frequently found members of the human gut microbiome, followed by aspartate 1-decarboxylases and glutamate decarboxylases. In addition, our sequence analyses of various AADCs demonstrated that a tetrad of amino acids in the PLP binding motif can provide functional identification for AADCs. We hypothesize that the diversity in AADCs and the microbes that harbor them has the potential to alter host metabolic outputs. This could provide a mechanism to use specific changes in microbial genera or species to understand possible metabolite modulations that might influence biological functions. Such studies could lay the groundwork for developing future disease markers or therapeutic interventions.